A Ismail Raji Al Faruqi's Thoughts on the Wiwitan Tradition in Kedak, Kediri - Muhammad Abdur Rozaq; Achmad Khudori Soleh (Tebuireng: Journal of Islamic Studies and Society, 2024)
This research was motivated by changes in the wiwitan tradition which then made relevance to Ismail Raji al-Faruqi's thoughts on social science, in which al-Faruqi's thoughts were associated with Tawhid which is the principle of social order. Tawhid not only emphasizes individual piety but also social piety. Because monotheism is the first determining principle in Islam, its culture and science. This study uses qualitative research with sociological methods, with data collection methods using instruments in the form of documents, interviews, and observations. This research finds some of al-Faruqi's thoughts about the principle of monotheism which is the social order in society. because monotheism is not for seeking the truth within oneself but for others as well, the concept of truth for oneself is just a waste. This is in line with the changes in values ​​in the wiwitan tradition, which produce values ​​from social, economic, religious and spiritual aspects. Which this tradition has a positive impact on religious social life, in terms of monotheism with the form of gratitude to the Almighty by giving alms in the form of giving food to others.